Antioxidant activities from different parts of Sargassum polycystum thalli through ultrasound-assisted extraction (UAE) method - Sumandiarsa, I Ketut; Hamida, Nurul; Santoso, Joko; Tarman, Kustiariyah (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
Sargassum polycystum is well known as macroalgae that contain active compounds with great function as antioxidants. The antioxidants content of the seaweed has links closely to phenolic compounds. The study is aimed to determine active compound quality from different thalli parts of S. polycystum extracted by Ultra-sound-assisted extraction (UAE). Fresh samples were prepared into three parts, which are apical, middle, and base thallus. Extraction was carried out by ultrasonication method and using 90% acetone as solvent. Levels of total phenols were analyzed using the Reagent Folin-Ciocalteu. Antioxidant activities were analyzed using DPPH, FRAP, and CUPRAC methods. The highest total phenolic content was found at the apical of the thallus, about 875.64 mg GAE/g. The most excellent DPPH antioxidant activities in S. polycystum were found from the apical part of the thallus with an IC 50 value of 38.49 ppm. The FRAP and CUPRAC antioxidant’s capacity showed the highest in the apical part of the thallus, which was 989.93 mol Fe (II)/g and 555.52 µmol Trolox/g, respectively. The extraction results of different parts of the thallus show highly potent active compounds of alkaloids, steroids, phenols, flavonoids, and potent antioxidants activity.Keywords: antioxidants, phytochemical, ultrasonication, S. polycystum